Designing the Transformation of Conventional to Digital Ordering with a QR Code-Based Website System at Mie Sop Ayam Kampung Kota Stabat - Andrean, Andrean Akbar Permana; Amin, Muhammad Amin; Hafni, Hafni (Bahasa Indonesia, 2025)
Small to medium-sized restaurants, such as mie sop ayam kampung in kota stabat, often face issues with order recording and daily transactions due to manual methods. This leads to slow service and inaccuracies in transaction records. To address these challenges, this study aims to design a QR Code-based food ordering system integratet with a website. This system allows customers to scan QR Codes at their tables, view digital menus, and place orders directly. The research uses the waterfall method, consisting of requirement analysis, design, implementation, testing, and maintenance phases. Each stage is carried out systematically to ensure that the system developed meets the operational needs of the restaurant. The results show that the QR Code-based ordering system improves operational needs of the restaurant. The results show that the QR Code-based ordering system improves operational efficiently. Based on these findings, it can be concluded that implementing Qr Code Technology in food ordering systems enhances efficiency and customer satisfaction while helping restaurants better manage their operations.